2020
DOI: 10.3390/pathogens9050367
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Epidemic Diarrhea Virus and the Host Innate Immune Response

Abstract: Porcine epidemic diarrhea virus (PEDV), a swine enteropathogenic coronavirus (CoV), is the causative agent of porcine epidemic diarrhea (PED). PED causes lethal watery diarrhea in piglets, which has led to substantial economic losses in many countries and is a great threat to the global swine industry. Interferons (IFNs) are major cytokines involved in host innate immune defense, which induce the expression of a broad range of antiviral effectors that help host to control and antagonize viral infections. PEDV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 234 publications
3
31
0
Order By: Relevance
“…A limitation of the current study is the lack of an analysis of the possible diarrhea-bytreatment interactions, although evidence has shown the interaction of host immune and diarrhea in humans and animals [23][24][25]. In the present study, it was well established that probiotics interacted with the host by modulating gut macrobiotic composition, altering nutrient metabolism in the intestine, or directly improving intestinal barrier function [26,27].…”
Section: Discussionmentioning
confidence: 85%
“…A limitation of the current study is the lack of an analysis of the possible diarrhea-bytreatment interactions, although evidence has shown the interaction of host immune and diarrhea in humans and animals [23][24][25]. In the present study, it was well established that probiotics interacted with the host by modulating gut macrobiotic composition, altering nutrient metabolism in the intestine, or directly improving intestinal barrier function [26,27].…”
Section: Discussionmentioning
confidence: 85%
“…It was initially reported in the United Kingdom and Belgium in the early 1970s, and a highly pathogenic variant strain was identified in 2010, which caused high morbidity of up to 100% in piglets. The threat of PEDV has been constant since then ( 8 10 ). With the lack of a basic understanding of PEDV infection and the emergence of highly pathogenic strains of PEDV, current antiviral therapeutic strategies cannot provide complete protection for PEDV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports showed that the S protein, the N protein and the accessory ORF3 protein also play an important role in regulating the virulence of PEDV strains and can cause severe damage by evading host immune mechanisms (Zhang & Yoo, 2016;Kim et al, 2020;Li et al, 2020). The N protein is identified as a multifunctional region and participating in many stages in viral replication and regulating functions of PEDV (Zuniga et al, 2010;Liwnaree et al, 2019).…”
Section: Discussionmentioning
confidence: 99%